Torsion of a parasitic myoma that developed after abdominal myomectomy - Cho, In Ae (Obstet Gynecol Sci, 2016)
Iatrogenic parasitic myomas are rare. The condition is defined by the presence of multiple smooth-muscle tumorous nodules in the peritoneal cavity. This may be attributable to seeding of myoma particles during uterine surgery. The clinical course is usually indolent. The disease is often asymptomatic and is usually discovered only incidentally. A 38-year-old woman who had undergone abdominal myomectomy 7 months prior presented with acute abdominal pain and a huge pelvic mass. We performed exploratory laparotomy. A parasitic mass 17 cm in diameter with a twisted omental pedicle was identified. En bloc excision of the mass and omentum was performed, followed by total abdominal hysterectomy. Histopathological examination of multiple sections revealed features compatible with an infarcted leiomyoma. Thus, we present a very rare case of an iatrogenic, rapidly growing parasitic myoma complicated by omental torsion (which caused the acute abdominal pain). We also offer a literature review.